Fundamental financial accounting concepts - Edmonds, Thomas P (McGraw-Hill Irwin, 2011)
Rev. ed. of: Fundamental financial accounting concepts / Thomas P. Edmonds ... [et al.]. 6th ed. 2008.;Includes index.